2010
DOI: 10.1016/j.ydbio.2010.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Dicer is required for survival of differentiating neural crest cells

Abstract: The neural crest (NC) lineage gives rise to a wide array of cell types ranging from neurons and glia of the peripheral nervous system to skeletal elements of the head. The mechanisms regulating NC differentiation into such a large number of cell types remains largely unknown. MicroRNAs (miRNAs) play key roles in regulating developmental events suggesting they may also play a role during NC differentiation. To determine what roles miRNAs play in differentiation of NC-derived tissues, we deleted the miRNA proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
107
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 46 publications
12
107
1
Order By: Relevance
“…The loss of the microRNA-processing enzyme dicer has been shown to severely reduce the survival of sympathetic neuron precursors (Huang et al 2010;Zehir et al 2010) and also partially to affect the establishment of their typical neuronal gene expression pattern (Stubbusch et al 2013). Notably, sympathetic neurons of dicer-deficient mouse embryos exhibit reduced expression levels of synaptic marker genes and thus become more reminiscent of wildtype chromaffin cells in this respect.…”
Section: Discussionsupporting
confidence: 85%
“…The loss of the microRNA-processing enzyme dicer has been shown to severely reduce the survival of sympathetic neuron precursors (Huang et al 2010;Zehir et al 2010) and also partially to affect the establishment of their typical neuronal gene expression pattern (Stubbusch et al 2013). Notably, sympathetic neurons of dicer-deficient mouse embryos exhibit reduced expression levels of synaptic marker genes and thus become more reminiscent of wildtype chromaffin cells in this respect.…”
Section: Discussionsupporting
confidence: 85%
“…Using a mouse with loss of neural crest-derived tissue, we have shown that the neural crest cartilage is needed for the formation of the mesodermally derived stapedial footplate, and in the absence of neural crest cartilage the oval window does not form correctly. In the Wnt1cre-Dicer mice, neural crest cells are able to migrate and are found within the same locations as in control littermates at E11 (Zehir et al, 2010), but cells do not differentiate into cartilage but undergo apoptosis (Huang et al, 2010;Zehir et al, 2010). It is possible, therefore, that the migrating neural crest cells at E11 are able to signal to the otic capsule, positioning the oval window before stapes differentiation.…”
Section: Neural Crest Part Of the Stapes Is Needed For Formation Of Tmentioning
confidence: 99%
“…For this, we took advantage of the Wnt1cre/Dicer mouse, which has been shown to lack cartilages of neural crest origin, including the stapes (Huang et al, 2010). In these mutants, migration of crest into the head appears normal, but the cells do not differentiate into cartilage and high apoptosis is observed in the mandible mesenchyme at E12.5 (Huang et al, 2010;Zehir et al, 2010). At E18.5, in the wild-type mouse the middle ear ossicles can be seen strongly stained with Alcian blue (Fig.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…[26] that both the dicer and miRNAs are required for the survival of neural crest-derived tissues by preventing apoptosis during differentiation because the dicer was essential for the differentiation process related to the neural crest cells survival, while neuronal crest needs specific hdac1 function during its development as shown in a series of zebrafish experiment [27]. In the trunk region, the ventrally migrating neural crest cells move through the somitic mesenchyme in a segmented pattern, presumably setting the basis for the sensory and sympathetic ganglia metameric organization along the anterior-posterior axis later in development [28].…”
Section: Genetics and Clinical Characteristicsmentioning
confidence: 99%